Radiometric patterns as a tool for separation of four grass species under "cerrado" conditions - Assad, Eduardo Delgado; Neto, José da Silva Madeira; Moreira, Lucimar (Pesquisa Agropecuaria Brasileira, 1991)
Research was conducted to establish the reflectance patterns of four pasture grasses: Brachiaria decumbens, Brachiaria humidicola, Brachiaria ruziziensis and Andropogon gayanus, in order to identify response for possible radiometric discrimination, their temporal evolution, and to study the relationship between biomass and reflectance. The results indicate a good separability of the grasses into two groups: A. gayanus and B. humidicola in the first group and B. ruziziensis and B. decumbens in the second one. A good correlation was found between reflectance and grass water content but no correlation was found between reflectance and biomass for the grasses studied.
Keywords: remote sensing; Brachiaria; Andropogon